Mobilizing black Germany Afro-German women and the making of a transnational movement - Florvil, Tiffany N. 1980- (University of Illinois Press, 2020)
"In the 1980s and 1990s, Black German women began to play significant roles in challenging the discrimination in their own nation and abroad. Their grassroots organizing, writings, and political and cultural activities nurtured innovative traditions, ideas, and practices. These strategies facilitated new, often radical bonds between people from disparate backgrounds across the Black Diaspora. Tiffany N. Florvil examines the role of queer and straight women in shaping the contours of the modern Black German movement as part of the Black internationalist opposition to racial and gender oppression. Florvil shows the multifaceted contributions of women to movement making, including Audre Lorde's role in influencing their activism; the activists who inspired Afro-German women to curate their own identities and histories; and the evolution of the activist groups Initiative of Black Germans and Afro-German Women. These practices and strategies became a rallying point for isolated and marginalized women (and men) and shaped the roots of contemporary Black German activism. Richly researched and multidimensional in scope, Mobilizing Black Germany offers a rare in-depth look at the emergence of the modern Black German movement and Black feminists' politics, intellectualism, and internationalism"--
Includes bibliographical references and index
Keywords: Afrodeutsche Frauen; Initiative Schwarze Menschen in Deutschland; Geschichte 1980-2000; Women, Black -- Political activity -- Germany; Women political activists -- Germany; Blacks -- Political activity -- Germany; Feminism -- Germany; Social movements -- Germany; African diaspora; Internationalism; Soziale Bewegung; Schwarze Frau; Deutschland; Hochschulschrift